2015
DOI: 10.4238/2015.december.22.17
|View full text |Cite
|
Sign up to set email alerts
|

miR-125a-5p expression is associated with the age of breast cancer patients

Abstract: ABSTRACT. Dysregulated miR-125 observed in multiple cancer types has suggested that it is involved in malignant proliferation and invasion. However, the clinical significance of miR-125 in human breast cancer (BC) has not yet been fully elucidated. In the present study, the expression of miR-125a-5p/3p and miR-125b in 143 pairs of BC and normal adjacent tissues (NATs) was measured by real-time quantitative PCR, and the correlation between expression and clinicopathological features was explored. miR-125a-5p a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…miRNA-125 (miR-125) is a highly conserved miRNA family identified in diverse species from nematodes to humans. miR-125 family members are downregulated in several diseases, such as various cancers [ 12 , 13 ]. However, miR-125-5p is highly expressed in mature glial cells but is downregulated in retinal neurons [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…miRNA-125 (miR-125) is a highly conserved miRNA family identified in diverse species from nematodes to humans. miR-125 family members are downregulated in several diseases, such as various cancers [ 12 , 13 ]. However, miR-125-5p is highly expressed in mature glial cells but is downregulated in retinal neurons [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, BDNF serves as a vital regulator of energy balance . Xu et al reported that miR‐125a‐5p served as a tumour suppressor by regulating the BRCA1 signalling in breast cancer cells, whereas He et al demonstrated that miR‐125a‐5p may play an important role in breast cancer progression in an age‐dependent manner . miR148a as one of the hypermethylated miRNAs exhibiting cancer‐specific methylation epigenetic is specifically and preferentially expressed in mouse epididymis .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, miR-192 was found to directly target SCARB1 mRNA in adipocytes (Mysore et al, 2016 ). Although no data on the role of these miRNAs in the context of SCARB1 and cancer is available, recent studies have shown that levels of miR-125a (Guo et al, 2009 ; He et al, 2015 ; Tong et al, 2015 ; Lee et al, 2016 ), miR-455 (Chai et al, 2015 ; Li et al, 2016 ), miR-185 (Qu et al, 2013 ; Fu et al, 2014 ; Tang et al, 2014 ; Li et al, 2015 ; Zhang et al, 2015 ), and miR-192 (Feng et al, 2011 ; Geng et al, 2014 ; Sun et al, 2016 ) are down-regulated in several types of cancer. These findings suggest that SCARB1 post-transcriptional regulation may be altered to promote SR-BI expression in cancer cells.…”
Section: Regulations Of Scarb1 Transcription and Smentioning
confidence: 99%